Will smart cities enhance the social capital of residents? The importance of smart neighborhood management. (August 2021) - Nakano, Satoshi; Washizu, Ayu
Abstract: Social capital is a concept that indicates the strength of the relationship among people inside and outside a community. It is a factor that facilitates policy for community formation and regeneration and is also an indicator of the outcome of a policy for improving a community. This study examined the hypothesis that the regional efforts to create smart cities using advanced ICT technologies enhance the social capital of the city and identified the factors that enhance social capital. Urban policy in Japan is shifting from hardware-oriented development to software-oriented area management; the Minato Mirai 21 district in the city of Yokohama is a typical example of area management. The essence of smart transition is to enhance various management functions by using smart social technologies, such as advanced information communication. The attractiveness of smart cities with sophisticated area management provided by such technologies will likely be high. Thus, this study's results will provide useful implications for better area management in smart cities. Highlights: Smart city-oriented area management improves regional social capital indicators. Essence of smart transition is to enhance various management functions by using ICT. In smart cities, ICTs are used to strengthen the communication between residents. Smart city-oriented area management should be promoted by arranging a top-down and bottom-up approach. Use of social capital indicators that are common ratings for both approaches is helpful.